CTA Annual Report 2004 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The concept behind the design of this annual report is channels of communication; channels along which ideas and experiences flow, reflecting CTA’s mandate to encourage the two-way flow of information through different medias.